Purification of native p94, a muscle-specific calpain, and characterization of its autolysis - Kayoko Kinbara; Shoichi Ishiura; Shigeo Tomioka; Hiroyuki Sorimachi; Seon-Yong Jeong; Susumu Amano; Hiroshi Kawasaki; Bernhard Kolmerer; Sumiko Kimura; Siegfried Labeit; Koichi Suzuki (1998)
p94, a skeletal muscle-specific calpain, has attracted much attention because its gene is responsible for limb-girdle muscular dystrophy type 2A. p94, however, has not been characterized at the protein and enzyme levels, owing to its very rapid autolysis. In the present study, a purification procedure for p94 was first established by using a recombinant inactive p94 expressed in COS cells in which the active site cysteine residue was changed to serine [p94(C129S)]. The isolation of native p94 from rabbit skeletal muscle by the established method with conventional procedures was extremely difficult because p94 became highly unstable in a crude extract on the addition of NaCl for separation. Purification of native p94 was possible with an antibody-affinity column but only as an inactive enzyme; p94(C129S) was purified as a homodimer. Characterization of p94, especially autolysis, was performed with partly purified native p94 and p94(C129S). The autolysis of p94, which consisted at least partly of an intermolecular reaction, proceeded in three consecutive steps; 60 and 58 kDa fragments were produced as intermediates before a stable 55 kDa fragment appeared. Autolysis of p94 was regarded as a degradative step rather than for the activation of the enzyme. All the autolysis cleavage sites were located in the p94-specific insertion sequence 1 region, which explains why p94 is unstable compared with the other calpains. The autolysis sites in p94 clearly showed a different specificity relative to the autolytic and proteolytic cleavage sites of the ubiquitous µ- and m-calpains, in its preference for residues at the P3 to P1´ sites, indicating a distinct substrate specificity and function for the muscle enzyme.